Aberrantly Expressed lncRNAs and mRNAs of Osteogenically Differentiated Mesenchymal Stem Cells in Ossification of the Posterior Longitudinal Ligament - Cai, Zhaopeng; Liu, Wenjie; Chen, Keng; Wang, Peng; Xie, Zhongyu; Li, Jinteng; Li, Ming; Cen, Shuizhong; Ye, Guiwen; Li, Zhaofeng; Su, Zepeng; Ma, Mengjun; et al. (Frontiers in Genetics, 2020)
Ectopic bone formation is the chief characteristic of ossification of the posterior longitudinal ligament (OPLL). Emerging evidence has revealed that long non-coding RNAs (lncRNAs) can regulate the osteogenic differentiation of mesenchymal stem cells (MSCs), which are the main cells responsible for bone formation. However, the role of lncRNAs in the pathogenesis of OPLL remains unclear. In this study, 725 aberrantly expressed lncRNAs and 664 mRNAs in osteogenically differentiated MSCs from OPLL patients (OPLL MSCs) were identified by microarrays and confirmed by qRT-PCR assays. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses showed that the most enriched pathways included the p53, JAK-STAT and PI3K-Akt signaling pathways. The coexpression network showed the interactions between the aberrantly expressed lncRNAs and mRNAs in OPLL MSCs, and the potential targets and transcription factors of the lncRNAs were predicted. Our research demonstrated the aberrantly expressed lncRNA and mRNA and the potential regulatory networks involved in the ectopic bone formation of OPLL. These findings imply that lncRNAs may play a vital role in OPLL, which provides a new perspective on the pathogenesis of OPLL.